2022
DOI: 10.1002/qj.4272
|View full text |Cite
|
Sign up to set email alerts
|

A satellite‐based climatology of fog and low stratus formation and dissipation times in central Europe

Abstract: Knowledge of fog and low stratus (FLS) cloud patterns and life cycles is important for traffic safety, for the production of solar energy and for the analysis of cloud processes in the climate system. While meteorological stations provide information on FLS, a data set describing FLS formation and dissipation times on large spatial and temporal scales does not yet exist. In this study, we use logistic regression to extract FLS formation and dissipation times from a satellite-based 10-year FLS data set covering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The basis of this study is a satellite-based FLS formation and dissipation time data set which contains information on the timing of the formation and dissipation of FLS for the years 2006-2015 over central Europe. This data set has been created by objectively identifying FLS formation and dissipation on a pixel-by-pixel basis and for each identified FLS event using logistic regression (Pauli et al, 2021;Pauli et al, 2022a). The data basis for this approach, described in Pauli et al (2022b), is an FLS data set derived from the Meteosat Spinning Enhanced Visible and InfraRed Imager (SEVIRI: Egli et al, 2017) with a spatial resolution of 5 km over central Europe.…”
Section: Fog and Low Stratus Formation And Dissipation Time Data Setmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis of this study is a satellite-based FLS formation and dissipation time data set which contains information on the timing of the formation and dissipation of FLS for the years 2006-2015 over central Europe. This data set has been created by objectively identifying FLS formation and dissipation on a pixel-by-pixel basis and for each identified FLS event using logistic regression (Pauli et al, 2021;Pauli et al, 2022a). The data basis for this approach, described in Pauli et al (2022b), is an FLS data set derived from the Meteosat Spinning Enhanced Visible and InfraRed Imager (SEVIRI: Egli et al, 2017) with a spatial resolution of 5 km over central Europe.…”
Section: Fog and Low Stratus Formation And Dissipation Time Data Setmentioning
confidence: 99%
“…Furthermore, fog is influenced by the underlying land‐surface type. An enhancement of fog occurrence has been found over forests (Pauli et al, 2022a), whereas fog cover is reduced in urban areas (Fuchs et al, 2022; Gautam & Singh, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Bergot et al (2015) relied on large eddy simulations (LESs) to characterise the role of dry downdrafts in allowing solar radiation to reach the ground and increase turbulence, leading to the dissipation. Additionally, Pauli et al (2022) studied the climatology of fog and low stratus cloud formation and dissipation times in central Europe using satellite data and showed that fog dissipation is also often related to topography. The dissipation processes are more difficult to study than the fog formation processes due to the complexity of fog's scale.…”
Section: Introductionmentioning
confidence: 99%